Pengaruh Kepemimpinan, Motivasi dan Disiplin Kerja terhadap Kinerja Karyawan - Alfian Alfian; Doni Afrial (JURNAL PUNDI, 2019)
This research aims to determine the leadership, motivation and work discipline of employees at PT Semen Padang. The sample in this study amounted to 50 employees. The statistical tool used is multiple linear regression (linear regression). Data were analyzed using SPSS 16 Statistical software. The result of the t test (partial) leadership significantly affect performance of employees with sig t 0.000 < 0.05 and 6.747 t-test value, motivation is not significantly affect performance of employees with sig t 0.783 > 0.05 and value of the t-calculate the value of -0.277, work discipline affect job performance of employees with sig t 0.032 < 0.05 and value of the t-test value of 2.212.